Pengembagan Permainan Tradisonal Gobak Sodor Bola dalam Pembelajaran Penjas pada Siswa SD - Setiawan, Ipang; Triyanto, Heri (Media Ilmu Keolahragaan Indonesia, 2014)
The purpose of this study was to produce a traditional game development Gobak Sodor ball. The method of this research is the development of research which refers to the model of development of Borg & Gall, namely: (1) to analyze the product to be developed that are obtained from the collection of information, observations and literature review, (2) develop the initial product form (form models traditional games gobak Sodor ball), (3) evaluation of the expert (one Penjas experts and learning experts penjasorkes two elementary schools), as well as small-scale trials (4) a large-scale trial, (5 ) revision of the final product. From the results of a small-scale test data showed that the expert evaluations, expert Penjas 80% (good), learning experts I 81.33% (good), learning experts II 82.67% (good), the results of a small-scale pilot questionnaire mean the average percentage of the appropriate answer choices 94.16% (very good), the average of large-scale trial questionnaire obtained the average percentage of the appropriate answer choices 92.11% (very good). From the available data it can be concluded that the model of the traditional game gobak Sodor this ball can be used for students for elementary school.